(untitled) (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The influence of the degree of pigmentation, shine, weight, and form index on the hatchability rate of quail eggs (Coturnix coturnix japonica) was examined. Materials and Methods: Three thousand three hundred eggs were incubated after they were classified according to the degree of shell pigmentation: high (HP), medium (MP), and low (LP); shell shine: shiny (SS), and opaque; Egg weight: <11, 11.0–11.9, 12.0–12.9, and >13 gm; form index: <78% and >78%. The Mann–Whitney non-parametric test for independent samples was used to evaluate hatching data. Results: Hatchability was best in eggs with HP and SS (p < 0.05): 69.2% and 75.7%, respectively; eggs with MP had the lowest hatchability rate (63.1%). The highest risk of embryo death (17.8%) was observed in eggs containing LP (p < 0.05). Eggs weighing between 12 and 12.9 gm had the highest hatchability rate (p < 0.05) (79.11%). Eggs with a form index >78% had the highest hatchability rate (p < 0.05) (67.62%). Conclusions: HP, MP shell eggs, and SS eggs with a weight of between 12.0 and 12.9 gm and a shape index of greater than 78% have a higher hatchability rate. J. Adv. Vet. Anim. Res., 8(4): 629–634, December 2021 http://doi.org/10.5455/javar.2021.h554